Historians and Slavery: A Critical Analysis of Perspectives and Irony in American Slavery, and Other Recent Works. - Wright, W. D. (1978)
Keywords: Genovese; Eugene D.; 1930-2012; Engerman; Stanley L; Perspectives and irony in American slavery; Slavery; Historiography; United States; dept.his; faculty_collection

Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978FQ74200055 tex.unique-id: [object Object]
Keywords: book.review; dept.his